2008
DOI: 10.1016/j.jadohealth.2007.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Alcohol and Drug Involvement in Hospitalized Adolescents with Assault Injuries

Abstract: Our methodology and findings contribute to the understanding of the epidemiology of assaultive behaviors and the role of alcohol/drug use in injury among adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…, 100) were generated from the SCTBIFR data so that a patient was in either onehalf of the ith sample or the other half, but not in both halves. 34 The first half of each sample (estimation set) was used to fit the model and the second half (validation set) was used to validate its corresponding first half. This process was exhaustive-each of the 2118 cases in the SCTBIFR data had the same probability of being selected for either the estimation or the validation set.…”
Section: Model Estimation and Validationmentioning
confidence: 99%
“…, 100) were generated from the SCTBIFR data so that a patient was in either onehalf of the ith sample or the other half, but not in both halves. 34 The first half of each sample (estimation set) was used to fit the model and the second half (validation set) was used to validate its corresponding first half. This process was exhaustive-each of the 2118 cases in the SCTBIFR data had the same probability of being selected for either the estimation or the validation set.…”
Section: Model Estimation and Validationmentioning
confidence: 99%
“…As many as two in three adolescents report having been exposed to psychological trauma (1), among which most include victimization, such as exposure to or witnessing of abuse or domestic or community violence (2)(3)(4)(5). A study conducted in North America with a nationally representative sample of youths aged 2 to 17 years reported that over half of the sampled individuals had experienced physical assault during the survey year; approximately 1 in 8 experienced childhood trauma; approximately 1 in 12 suffered from sexual victimization; and as many as 1 in 3 had witnessed some form of violence (6).…”
mentioning
confidence: 99%
“…Alcohol and other substance use by adolescents is another major risk factor for violence victimisation 10,11 . Young people, especially males, are more likely to be victims of alcohol or drug‐related interpersonal violence than any other age group 12 .…”
mentioning
confidence: 99%
“…Young people, especially males, are more likely to be victims of alcohol or drug‐related interpersonal violence than any other age group 12 . An analysis of American adolescents aged 10–20 years who were hospitalised for assault injuries predicted the proportion of drug‐/alcohol‐related cases to be from 54% to 66% 11 . The literature also indicates that adolescents with mental illness and low self‐esteem are at increased risk of interpersonal violence 13–15 …”
mentioning
confidence: 99%
See 1 more Smart Citation